Differences in Platelet Count Results Based on Storage Time of Modified Dyes with Phosphate Buffer Saline Solvent pH 7.3 - Gilang Nugraha; Muhammad Rizqi Cahyadi (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2026)
Laboratory tests must be performed properly in accordance with procedures to obtain accurate, precise, fast, and reliable results, as there is high demand from doctors for assistance in establishing diagnoses, particularly for platelet disorders. This study aims to determine the differences in platelet counts based on the storage time of modified Safranin staining reagents with PBS pH 7.3 solvent. This experimental study compared a control group using Rees Ecker reagent and an intervention group using modified reagent, with observations on days 0, 1, 7, and 14. The average platelet count using Rees Ecker reagent yielded a result of 323,000 cells/mm³. The mean platelet count using the modified reagent was 337,085 cells/mm³. The mean platelet count was calculated using the Improved Neubauer counting chamber. Statistical analysis using One Way ANOVA yielded a p-value of 0.060, indicating no significant difference between the two groups regarding reagent storage time.